Jaskółka zwiastująca wiosnę czy relikt przeszłości? Z badań nad atrakcyjnością słuchowiska radiowego - Albińska, Karolina (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
This article is an empirical exploratory investigation into the problem of “old radio genres’” reception by contemporary listeners. The paper focuses particularly on the radio drama, very popular in the Golden Age of Radio and now on the verge of disappearing. The transformation of media environment, due to the media convergence process, has enormous impact on the changes in the mass media hierarchy. This issue has inspired a survey conducted among journalism students asking them about their listening behaviours and radio programmes preferences. The main purpose of this research was to assess whether radio dramas sill can be attractive to contemporary radio listeners. The results of the survey not only help to determine the place of radio – until recently the only transmitter of artistic radio programmes – in the media, but also assess the degree of contemporary listeners’ attachment to audio theatre plays.